A systematic analysis and future projections of the nutritional status and interpretation of its drivers among school-aged children in South-East Asian countriesResearch in context - Md. Mizanur Rahman; Angela de Silva; Miho Sassa; Md. Rashedul Islam; Sarmin Aktar; Shamima Akter (Elsevier, 2023)
Summary: Background: Nutrition inadequacy during childhood and adolescence can cause suboptimal growth, intergenerational effects on offspring and an increased risk of chronic diseases in adulthood. There is little information on the prevalence and drivers of malnutrition in children aged 5-19 years, in the South-East Asian setting, since most existing interventions have to date targeted undernutrition. We assessed the national prevalence of nutritional indicators, their trends, and associated risk factors among children aged 5-19 years from 11 countries of WHO South-East Asia Region (SEA Region) in order to provide evidence to guide future policy direction. Methods: We included 5,210,646 children for analysis from 345 studies and 25 survey datasets. A Newcastle-Ottawa Scale was used to assess the quality of the study. Bayesian regression models were used to estimate the prevalence of malnutrition between 2000 and 2030, and a series of subgroup analyses were performed to assess variation in pooled estimates by different socio-demographic and lifestyle factors. The protocol was registered with PROSPERO database (CRD42023400104). Findings: Overall, pooled analysis demonstrated that indicators of undernutrition in SEA is predicted to decrease between 2000 and 2030 including stunting (36.6%-27.2%), thinness (29.5%-6.2%), and underweight (29.2%-15.9%). However, a substantial increase in prevalence of overweight (6.0% in 2000-16.9% in 2030), and obesity (2.6%-9.5%) are predicted. The prevalence of micronutrient deficiencies between 2000 and 2030 is predicted to decrease-vitamin A by 84% and vitamin D by 53%. Parents' education levels and household wealth were inversely associated with malnutrition. Children's health-related behaviours, such as unhealthy dietary habits and spending more time watching TV, playing games, or using the computer, were associated with increased chance of overweight and obesity. There were no clear signs of publication bias in our study. Interpretation: Our analysis highlights the pattern of a double burden of malnutrition, with clear differences between different socio-demographic groups. Despite a substantial reduction in the prevalence of stunting, underweight, and anaemia since 2000, an emerging increase in overweight/obesity and micronutrient deficiencies warrants urgent attention. Funding: World Health Organization Regional Office for South-East Asia New Delhi, India.